Indigenisation of English: A Sociolinguistic Study of Automobile Jargons in Pakistani Context - Naeem, Muhammad; Muhammad Haseeb Nasir (University of Chitral Journal of Linguistics and Literature, 2023)
This study explores the phenomenon of language contact and investigates how English lexicon is being indigenized in Pakistani context. The researches have conceptualized the model given by Kachru (1983) to understand the nature of indigenization of English in the context of automobile jargons and further explored how the variation in language use is being an aid for the development of Pakistani English as a distinctive variety. This study targeted 60 vocabulary items related to automobile jargon and investigated the nature of variation in the selected lexical items in terms of their use in Pakistani context by collecting data from automobile mechanics in Rawalpindi, Pakistan. The researchers found that contact of English with local languages is reshaping features of English at phonological, lexical and grammatical level. The researchers found phonological, lexical and grammatical deviation and coinage of new and locally rooted terms for a number of English lexical items. The vocabulary items are indigenized by receiving the shade of local languages. The findings of this study attest the presence of a new variety of English which strengthens Kachru’s stance that new and indigenized varieties of English are being established in non-native contexts as the result of contextualized contact between English and local languages.